GhHAI2, GhAHG3, and GhABI2 Negatively Regulate Osmotic Stress Tolerance via ABA-Dependent Pathway in Cotton (Gossypium hirsutum L.) - Shazadee, Hamna; Khan, Nadeem; Wang, Lu; Wang, Xinyu (Frontiers in Plant Science, 2022)
The type 2C protein phosphatases (PP2Cs) are well-known for their vital roles in plant drought stress responses, but their molecular mechanisms in cotton (Gossypium hirsutum L.) remain largely unknown. Here, we investigated the role of three clade A PP2C genes, namely GhHAI2, GhAHG3 and GhABI2, in regulating the osmotic stress tolerance in cotton. The transcript levels of GhHAI2, GhAHG3 and GhABI2 were rapidly induced by exogenous abscisic acid (ABA) and polyethylene glycol (PEG) treatment. Silencing of GhHAI2, GhAHG3 and GhABI2 via virus-induced gene silencing (VIGS) improved osmotic tolerance in cotton due to decreased water loss, increase in both relative water content (RWC) and photosynthetic gas exchange, higher antioxidant enzyme activity and lower malondialdehyde (MDA) content. The root analysis further showed that GhHAI2, GhAHG3 and GhABI2-silenced plants were more responsive to osmotic stress. Yeast two-hybrid (Y2H) and luciferase complementation imaging (LCI) assays further substantiated that GhHAI2, GhAHG3 and GhABI2 interact with the core receptors of ABA signaling, GhPYLs. The expression of several ABA-dependent stress-responsive genes was significantly up-regulated in GhHAI2, GhAHG3 and GhABI2-silenced plants. Our findings suggest that GhHAI2, GhAHG3, and GhABI2 act as negative regulators in the osmotic stress response in cotton through ABA-mediated signaling.